Readmission Trends Related to Unruptured Intracranial Aneurysm Treatment - Mehta, Tapan; Desai, Ninad; Patel, Smit; Male, Shailesh; Khan, Adam; Grande, Andrew Walker; Tummala, Ramachandra Prasad; Jagadeesan, Bharathi Dasan (Frontiers in Neurology, 2021)
Background and Purpose: Aneurysmal subarachnoid hemorrhage (SAH) is associated with high mortality. Prophylactic treatment of the unruptured intracranial aneurysm (UIA) is considered in a select group of patients thought to be at high for aneurysmal rupture. Hospital readmission rates can serve as a surrogate marker for the safety and cost-effectiveness of treatment options for UIAs; we present an analysis of the 30-day rehospitalization rates and predictors of readmission following UIA treatment with surgical and endovascular approaches. Methods: We retrospectively analyzed data from the National Readmission Database (NRD) derived from the Healthcare Cost and Utilization Project for the year 2014. The cohort included patients with a primary discharge diagnosis of a treated unruptured aneurysm. The primary outcome variable was the 30-day readmission rate in open surgical vs. endovascularly treated groups. The secondary outcomes included predictors of readmissions, and causes of 30-day readmissions in these two groups. Results: The 30-day readmission rate for the surgical group was 8.37% compared to 4.87% for the endovascular group. The index hospitalization duration was longer in the surgical group. A larger proportion of the patients readmitted following surgical treatment were hypertensive (76.35, vs. 63.43%), but the prevalence of other medical comorbidities was comparable in the two treatment groups. Conclusions: There is a higher likelihood for 30-day readmission, longer duration of initial hospitalization and a lower likelihood of discharge home following surgical treatment of UIAs when compared to endovascular treatment. These findings, however, do not demonstrate long-term superiority of one specific treatment modality.